AMINO ACID BINDING TO AFLATOXIN B1 DURING A NOVEL FOOD TREATMENT PROCESS PROTECTS AGAINST GENOTOXICITY - Rushing, Blake Richey (East Carolina University, 2018)
Access to clean food is a crucial factor in maintaining public health. Contamination of food supplies with toxic substances can lead to a myriad of health issues. As a mycotoxin, aflatoxin B1 (AFB1) is a naturally occurring toxin that contaminates a staggering amount of the world's food supply. Even more concerning is that AFB1 is a class 1 carcinogen and contributes heavily to the development of the world's incidence of hepatocellular carcinoma. Many strategies have been developed to detoxify contaminated food in an attempt to mitigate AFB1 exposure, however this has been met with limited success. This dissertation covers our knowledge of AFB1's toxicity, the current state of AFB1 occurrence in food, and previous detoxification strategies along with their advantages and disadvantages. Our experimental goals were to investigate the potential of a novel detoxification strategy that utilizes the formation of a nontoxic intermediate, aflatoxin B2a (AFB2a). The chemical reaction between AFB2a and amino acids was evaluated and incorporated into the treatment process to produce a novel detoxification product, abolishing the characteristic genotoxicity of AFB1. This process was carried out using additives that are approved for human consumption with a method that does not require complex equipment. Additionally, this process removed all detectable levels of AFB1 on artificially contaminated corn, forming only a single product. These properties offer great advantages over previously proposed detoxification methods which lends a great potential for this treatment method to be used by various populations to provide clean and safe foods.
Keywords: mycotoxins; detoxification; hepatocellular carcinoma; liquid chromatography; mass spectrometry; mutagenicity; food safety; Aflatoxin B1; Protective Agents; Food; Food Handling; DNA Damage; Amino Acids